Peran Agresivitas Pajak dalam Strategi Keuangan Perusahaan: Analisis terhadap Ukuran, Leverage, dan Profitabilitas - Maudy, Naura (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Tax aggressiveness has been a major focus in the corporate finance literature, because it influences strategic decisions related to tax payments and corporate financial performance. Previous studies show that tax aggressiveness can interact with factors such as company size, leverage, and profitability, but not many studies have specifically analyzed this relationship. This research aims to analyze the role of tax aggressiveness in a company's financial strategy with a focus on its effect on company size, leverage and profitability. The method used in this research is multiple regression analysis of financial data from a number of companies spread across various industrial sectors. Data was collected from the company's annual financial reports and analyzed using statistical software. The results of the analysis show that tax aggressiveness has a significant impact on the company's financial strategy, by influencing size, leverage and profitability. These findings indicate that firms tend to adopt certain financial strategies to optimize their tax benefits.